Failure analysis of M400 alloy distributor of top gas scrubber in alkane dehydrogenation unit. (August 2022) - Liu, Shuai; Wang, Lida; Yan, Zhenxing; Zhang, Piji; Sun, Wen; Yang, Zhengqing; Li, Hejin; Hao, Anfeng; Bao, Xuewei; Liu, Guichang
Highlights: Corrosion causes of M400 alloy distributor were studied by experiment and CFD. The distributor suffers from serious scouring effect of high-speed corrosive media. Introduced Fe 3+ and sulfide promoted the corrosion of the distributor commonly. A mutually vicious circle is built by the corrosion of the distributor and scrubber. Abstract: M400 alloy distributor used to disperse acid gas containing HCl and H2 S in the stabilizer top gas scrubber suffers from severe corrosion attack at the connection between distribution pipe, branch pipe and distribution hole during service. The failure analysis is carried out through experimental and numerical simulation methods. The results show that the acidic gas has scouring effect, and the corrosion products in the front gas transmission pipeline are brought into distributor by high-speed airflow and promote its corrosion. In addition, dew-point corrosion on the scrubber wall and the entrance of oxidized Fe 3+ into the distributor, further aggravate its erosion corrosion. The erosion corrosion of the distributor and the dew-point corrosion of the scrubber wall build a vicious cycle in common, which eventually leads to the failure of the distributor. A series of protection suggestions are put forward to mitigate and avoid similar incidents.